Contended borders: selective closures and solidarity initiatives - Ambrosini, Maurizio (2022)
The article has two objectives. First of all, it intends to deepen the theme of the return of borders, illustrating its articulation at different levels and its selective functioning, as an effect of a neo-liberal regime of government of human mobility: a regime that incorporates profound inequalities in the distribution of the right to move across borders. The case of push-backs at the border with Bosnia and the responsibility of the Frontex agency will be investigated to illustrate the functioning of border surveillance by the EU. The pandemic has also favored the strengthening of measures to restrict theaccess of unwanted migrants in developed countries. Secondly, the article looks at the actors and initiatives that try to open spaces of solidarity and welcome towards migrants and asylum seekers, challenging on a practical level the absolutization of borders and the exclusion of those who knock on gates to the North...